Pedagogical Content Knowledge (PCK) Mathematics Pre-service Teachers in Developing Content Representations (CoRes) - Suripah, Suripah; Suyata, Suyata; Retnawati, Heri (International Journal on Emerging Mathematics Education, 2021)
This study aimed to determine the pedagogical content knowledge (PCK) of pre-service teachers in developing CoRes as a support for designing mathematics learning. Data were collected by reviewing documents of CoRes development results by 32 pre-service teachers after analyzing school mathematics learning documents in the form of syllabi and lesson plans prepared by experienced teachers. The analysis of the results of the pre-service CoRes document made by the pre-service teachers is done using descriptive statistics that are by calculating the mean. The results of the data analysis show that 18.8% of the pre-service teachers achieved very good qualification, 56.3% with good qualification, 15.6% with sufficient qualification, and 9.4% with poor qualification. Although there were still pre-service teachers belonged to the poor qualification, there were no pre-service teachers who failed in developing CoRes. Some individual students still seem to have difficulty developing CoRes. However, the CoRes document that has been prepared is very useful for carrying out further activities. Thus, it can be concluded that the development of CoRes can be used by pre-service teachers as a support to design learning.